Species distribution, hybridization and connectivity in the genus Chionodraco: Unveiling unknown icefish diversity in antarctica. Issue 5 (19th February 2021) - Schiavon, Luca; Dulière, Valérie; La Mesa, Mario; Marino, Ilaria Anna Maria; Codogno, Giuditta; Boscari, Elisa; Riginella, Emilio; Battistotti, Alessandra; Lucassen, Magnus; Zane, Lorenzo; Papetti, Chiara
Abstract: Aim: The species of the genus Chionodraco (Notothenioidei) are the most abundant icefish on the continental shelf of the Weddell Sea. While previous studies indicated that only Chionodraco hamatus and Chionodraco myersi inhabit the Weddell Sea, the third Chionodraco species, Chionodraco rastrospinosus, was recently sampled in the area. As C. rastrospinosus is supposed to be found only at the Antarctic Peninsula and Scotia Arc, this study aimed at confirming the species classification of C. rastrospinosus by molecular methods and identifying its putative source population. Given the documented evidence of introgression among the three species, we tested whether the newly found C. rastrospinosus shared any genetic variability with the other Chionodraco species. To explain the pattern of distribution of the Chionodraco species, we aimed at estimating the hydrodynamic connectivity between the Antarctic Peninsula and the Weddell Sea. Location: Antarctic Peninsula, southern Scotia Arc and the south‐eastern Weddell Sea. Methods: We genotyped 19 microsatellites and sequenced the mitochondrial D‐loop for 560 Chionodraco individuals. We simulated the dispersal of more than 3 million drifters (Lagrangian model). Results: The molecular analyses support the presence of C. rastrospinosus in the Weddell Sea and its homogeneity with C. rastrospinosus from the Antarctic Peninsula. Bayesian clustering identifies three putative hybrids among C. rastrospinosus and the other congenerics. Lagrangian simulations do not support connectivity driven by the oceanographic features of the Antarctic Peninsula and Weddell Sea via passive larval dispersal only. Main conclusions: This study documents, for the first time, the presence of C. rastrospinosus in the Weddell Sea unveiling more biodiversity than previously known in this region. The sympatry of the three Chionodraco species explains the occurrence of occasional, ongoing events of hybridization in the genus. Alternative possible hypotheses need to be tested in future studies about the mechanisms maintaining the interspecific connectivity in Chionodraco spp.